Dakwah and Conflict Resolution in Palu City: Religious Authorities and Habib Ratan Agency : (Sunnah Living Perspective) - Rahim, Muhammad Rafiiy; Hamdani, Fikri; Said, Muhammad (STAIN Majene, 2025)
This study analyzes the construction of religious authorities and religious leaders' agencies in the resolution of social conflicts through the perspective of living sunnah, with a case study of the role of Habib Rotan in the conflict of the Manunda Presidential Market, Palu City. This study criticizes the dominant perspective that positions religion as a trigger for conflict by affirming its role as a source of religious peacebuilding. The research employs a qualitative approach that includes case studies within the framework of religious authority theory, structuring theory, and living sunnah. Data were obtained through observation, interviews, documentation, and literature studies and then analyzed using the Miles and Huberman model. The results of the study show that religious authority is formed through the dialectic of genealogical capital, scientific legitimacy, social charisma, and the institution of the dhikr assembly. Religious agencies are carried out through soft power strategies, collaborative mediation, and internalization of the values of ishlah, tasamuh, and rahmah, thereby strengthening the social cohesion of multicultural communities.